2023
DOI: 10.1101/2023.12.29.573624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating genomic prediction strategies for grain carotenoid traits in a tropical/subtropical maize panel

Mary-Francis LaPorte,
Willy B. Suwarno,
Pattama Hannok
et al.

Abstract: Vitamin A deficiency remains prevalent on a global scale, including in regions where maize constitutes a high percentage of human diets. One solution for alleviating this deficiency has been to increase grain concentrations of provitamin A carotenoids in maize (Zea maysssp.maysL.)—an example of biofortification. The International Maize and Wheat Improvement Center (CIMMYT) developed a Carotenoid Association Mapping panel of 380 inbred lines adapted to tropical and subtropical environments that have varying gra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…It was found that some single nucleotide replacements, revealed in genome-wide genotyping, have a statistical association with the allelic state of carotenoid pathway genes and the content of carotenoids in maize grain (Diepenbrock et al, 2021). In some studies, along with classic markers of the allelic state of the β-carotene hydroxylase 1 and lycopene-ε-cyclase genes, namely crtRB1-3´TE, crtRB1-5´TE, crtRB1-InDel14, lcyE-3´INDL, lcyE-5´INDL, lcyE-SNP216, single nucleotide substitutionsin these genes were signifi cant for the same plant (Maazou et al, 2023;Sserumaga et al, 2019;Kondwakwenda et al, 2020;LaPorte et al, 2023;Azmach et al, 2018;Kebede et al, 2021). LaPorte et al ( 2023) concluded that when genome-wide markers were used, the accuracy of genomic prediction for the carotenoid content in maize grain was higher than when only the markers proximal to two carotenoid-related genes were used.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that some single nucleotide replacements, revealed in genome-wide genotyping, have a statistical association with the allelic state of carotenoid pathway genes and the content of carotenoids in maize grain (Diepenbrock et al, 2021). In some studies, along with classic markers of the allelic state of the β-carotene hydroxylase 1 and lycopene-ε-cyclase genes, namely crtRB1-3´TE, crtRB1-5´TE, crtRB1-InDel14, lcyE-3´INDL, lcyE-5´INDL, lcyE-SNP216, single nucleotide substitutionsin these genes were signifi cant for the same plant (Maazou et al, 2023;Sserumaga et al, 2019;Kondwakwenda et al, 2020;LaPorte et al, 2023;Azmach et al, 2018;Kebede et al, 2021). LaPorte et al ( 2023) concluded that when genome-wide markers were used, the accuracy of genomic prediction for the carotenoid content in maize grain was higher than when only the markers proximal to two carotenoid-related genes were used.…”
Section: Discussionmentioning
confidence: 99%